Women's Education from the Perspective of Islamic Philosophy of Education: Between Values and Patriarchy - Izzatussyakira; Nazli Azwany; Azizah Hanum OK (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
gender. This study aims to analyze and provide a philosophical perspective on Islamic education regarding the study of women's education, which is trapped between pure religious values and deeply rooted patriarchal culture. This study uses library research with a descriptive qualitative approach. Data collection techniques used documentation studies, then analyzed using content analysis techniques with the stages of data reduction, grouping, interpretation, and synthesis. The results show that Islamic education views women as subjects with potential and rights equal to those of men. Islamic education also serves as a filter, a forum, and a safe space for women to understand, express themselves, and develop critical awareness of their true role. Therefore, internal and external reconstruction is needed in the educational realm. Reconstruction of teaching materials, curriculum, learning methods, environmental culture, and government policies and institutional power holders is highly desirable. Thus, women's education can truly transform completely without repeating existing history.